Intelligent Trolley based on Internet of Things - Rajesh, D; Cindhuja, S; DhivyaLakshmi, K; P. Jaisheela (International Journal of Computer Sciences and Engineering, 2020)
Every-day is a development of new technology and it creates a revolution in society. The Internet of things is used to combine many devices and communicate with each other to do a specific task. In this paper, we describe a smart system used in supermarkets or shopping malls. Smart trolley with RFID is used to facilitate the users and to know the amount of the purchased items in the trolley. The current system will scan and add the items using microcontrollers. In the existing system, there is a chance of theft activity or if the product does not scan properly and it creates a loss of data. To overcome the drawbacks we proposed a smart trolley with RFID, Arduino Nano, Node MCU esp8266, GSM module which will perform scanning, adding of items, removing of items and theft checking using a load cell and also sends a notification to the mobile user.